Modernization’s Effect of Tax Administration System, Social Norms, Trust in the Government on Taxpayer Compliance in KP2KP Kutacane - Sri Devi; Ali Usman Siregar; Warsani Purnama Sari (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
This study aims to determine the influence of modernization of the tax administration system, social norms, trust in the government in taxpayer compliance at the Kutacane Tax Service, Counseling and Consultation Office (KP2KP). This type of research is an associative type of research. The population of this study was 2120 individual taxpayers registered at the Kutacane Tax Service, Counseling and Consultation Office (KP2KP) with a sample of 95 respondents with incidental sampling techniques. The type of data used is a quantitative data type. The source of this research data is primary data with data collection techniques through the dissemination of questionnaires. The data analysis techniques used in this study are descriptive statistical tests, data quality tests: validity and reliability tests, classical assumption tests: normality tests, multicholinearity tests and heteroskedasticity tests, multiple regression analysis, hypothesis tests: t statistical tests, f tests, determination coefficient tests and tests carried out using IBM SPSS software version 25. The results showed that partially the modernization of the tax administration system had a positive and significant effect on the compliance of individual taxpayers. Social norms and trust in the government have no influence on the compliance of individual taxpayers. Simultaneously the modernization of the tax administration system, social norms and trust in the government together positively affect the compliance of individual taxpayers